Design,fabrication and experimental study of a mini alkaline fuel cell for micro-electronic and mechanical application - Hon, Kah Jui (Universiti Malaysia Sarawak (UNIMAS), 2004)
This project is to design and fabricate a micro dissolved alkaline fuel cell for generating a small amount of electricity. The voltage generated had been proven to be useful for micro-electronic and mechanical signal application i.e. Pico scope. The Pico Scope can be function as a detector to detect unwanted signal such as interference.